1996
DOI: 10.1007/bf00663011
|View full text |Cite
|
Sign up to set email alerts
|

Reversal effect of itraconazole on adriamycin and etoposide resistance in human leukemia cells

Abstract: Itraconazole is a triazole antifungal agent that inhibits cell membrane serol biosynthesis. Currently, itraconazole is a potent candidate for in vivo use to revert multidrug resistance in acute leukemias, with the added benefit of its antifungal effect. As previously reported, itraconazole, as well as verapamil, reversed adriamycin-resistant K562 cells (K562/ADR) and HL60 cells (HL60/ADR) in dosages compatible to the plasma levels achieved by the therapeutic dosages used for the treatment of fungal infections.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…The mechanism of the itraconazole-methylprednisolone interaction is probably inhibition of CYP3ACmediated metabolism of methylprednisolone. However, itraconazole can also inhibit P-glycoprotein (Kurosawa et al 1996), a transmembrane efflux pump, and methylprednisolone has been recently shown to be a P-glycoprotein substrate (Saitoh et a/. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the itraconazole-methylprednisolone interaction is probably inhibition of CYP3ACmediated metabolism of methylprednisolone. However, itraconazole can also inhibit P-glycoprotein (Kurosawa et al 1996), a transmembrane efflux pump, and methylprednisolone has been recently shown to be a P-glycoprotein substrate (Saitoh et a/. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In the 1990s, itraconazole was demonstrated to reverse chemoresistance in cancer cells overexpressing P-gp ( Fig. 1; Table I) (4)(5)(6). In addition, the human breast cancer resistance protein is also inhibited by itraconazole (7).…”
Section: Preclinical Datamentioning
confidence: 99%
“…Itraconazole can also reverse resistance to the P-gp substrate daunorubicin (DNR) in a murine acute leukemia cell line in vitro (multidrug-resistant cells) (13), while the methylthiazolyl diphenyltetrazolium bromide (MTT) cytotoxicity assay results suggest an interaction of itraconazole with MDR and/or multidrug resistance protein (MRP)-associated resistance because of resistance reversal (18). The transport of vinblastine, DNR, and doxorubicin is affected by 100 M itraconazole in cells transfected with MDR1 cDNA (31).…”
mentioning
confidence: 99%